Group‐based cognitive behavioural psychotherapy for children and adolescents with ASD: the randomized, multicentre, controlled SOSTA – net trial. (30th December 2015) - Freitag, Christine M.; Jensen, Katrin; Elsuni, Leyla; Sachse, Michael; Herpertz‐Dahlmann, Beate; Schulte‐Rüther, Martin; Hänig, Susann; von Gontard, Alexander; Poustka, Luise; Schad‐Hansjosten, Tanja; Wenzl, Christina; Sinzig, Judith; et al.
Abstract : Background: Group‐based psychotherapy in Autism Spectrum Disorder (ASD) has predominantly been studied in the United States by small studies in school‐aged children without long‐term follow‐up. We report results of a large, confirmatory, multicentre randomized‐controlled phase‐III trial in children and adolescents studying the ASD specific, manualized group‐based cognitive behavioural SOSTA‐FRA approach. Methods: High‐functioning ASD individuals aged 8–19 years old were randomized to 12 sessions SOSTA‐FRA or treatment as usual. Primary outcomes were change in total raw score of the parent‐rated Social Responsiveness Scale (pSRS) between baseline (T2) and end of intervention (T4), and between T2 and 3 months after end of intervention (T5). Trial registration: ISRCTN94863788. Results: Between 20/5/2010 and 14/2/2013, n  = 320 ASD patients were screened, n  = 228 patients were randomized, and N  = 209 analysed. Mean pSRS difference between groups at T4 was −6.5 (95% CI −11.6 to – 1.4; p  = .013), and at T5 −6.4 (−11.5 to −1.3, p  = .015). Pre‐treatment SRS and IQ were positively associated with stronger improvement at T4 and T5. Conclusions: Short‐term ASD‐specific add‐on group‐based psychotherapy has shown postintervention efficacy with regard to parent‐rated social responsiveness predominantly in male high‐functioning children and adolescents with ASD. Future studies should implement blinded standardized observational measures of peer‐related social interaction.